Konference velvyslanců v červenci 1920 o Těšínsku, Oravě a Spiši v proměnách české historiografie - Aleš Binar (Theatrum Historiae)
The aim of study is to analyse changes of interpretation of events connected with decision made on conferences in June 1920 that marked out Czechoslovak-Polish borders. According to this decision disputed territories of Teschen Silesia, Orava, and Zips were divided into Czechoslovakia and Poland in way that new state borderlines went through all three regions. Study considers changes of point of view of Czech historiography on selected events regarding Spa decision and context of these changes from the beginnings of professional historical interest up to the present day.